2020
DOI: 10.1002/jmv.26606
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of NEAT1, IFNG‐AS1, and NRIR expression in Crimean–Congo hemorrhagic fever

Abstract: Crimean–Congo hemorrhagic fever (CCHF), whose causative agent is CCHF orthonairovirus (CCHFV), demonstrates different symptoms in patients. Long noncoding RNAs (lncRNAs) take part in various pathological processes of viral diseases. They are prominent regulators of antiviral immune responses. To our knowledge, this study is the first study to investigate nuclear paraspeckle assembly transcript 1 (NEAT1), interferon (IFN) gamma antisense RNA 1 (IFNG‐AS1), and negative regulator of IFN response (NRIR) expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…NEAT1 is a well-studied lncRNA known to play important anti-viral roles. In most studies, however, NEAT1 is upregulated upon viral infections (Prinz et al 2019) and downregulation has only been described in dengue and Crimean Congo hemorrhagic fever (Pandey et al 2017;Bayyurt et al 2021). Our results suggest that NEAT1 depletion may be specific to severe hemorrhagic fevers and it is the first time that such downregulation is shown to occur specifically in monocytes.…”
Section: Cell-type Dynamic Regulation Of Lncrnas Upon Ebov Infectionmentioning
confidence: 58%
“…NEAT1 is a well-studied lncRNA known to play important anti-viral roles. In most studies, however, NEAT1 is upregulated upon viral infections (Prinz et al 2019) and downregulation has only been described in dengue and Crimean Congo hemorrhagic fever (Pandey et al 2017;Bayyurt et al 2021). Our results suggest that NEAT1 depletion may be specific to severe hemorrhagic fevers and it is the first time that such downregulation is shown to occur specifically in monocytes.…”
Section: Cell-type Dynamic Regulation Of Lncrnas Upon Ebov Infectionmentioning
confidence: 58%
“…6a). NRIR and BISPR transcripts are virus-responsive lncRNAs involved in the regulation of the innate immune response and interferon signaling [52, 68]. MIR155HG has been also described as a regulator of the cellular response against influenza viruses [53] and recently characterized as upregulated in a cellular model of SARS-CoV-2 infection [69].…”
Section: Resultsmentioning
confidence: 99%
“…Using in vitro models of hepatitis C virus (HCV) infection, the knockdown of NRIR gene resulted in a marked reduction in HCV replication in interferon-stimulated hepatocytes, suggesting that it could affect the antiviral role of interferon [82]. In other viral infections such the Crimean-Congo hemorrhagic fever, NRIR has been also shown to be upregulated [68]. The molecular partners associated with NRIR regulatory action are still not characterized, however preliminary evidence suggested that NRIR could act via recruitment of chromatin-remodeling enzymes [51, 82].…”
Section: Discussionmentioning
confidence: 99%
“…Also, NEAT1 levels were negatively correlated with dengue severity ( Pandey et al, 2017 ). In addition, Bayyurt and his group found that NEAT1 was down-regulated in Crimean–Congo hemorrhagic fever (CCHF) patients and fatal groups compared with controls ( Bayyurt et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%